Determining tourist attitude towards responsible tourism in Melaka as world heritage site: design and validation of responsible heritage tourism scale / Faizah Abd Rahim … [et al.] - Abd Rahim, Faizah; Hassan, Faridah; Teo, Carol, Boon Chui; Mohd Khan, Noor Rita; Chuah, Soo Cheng (Research Management Institute (RMI), 2013)
The tourism industry holds huge potential for Melaka with its inception as World Heritage Site (WHS) by UNESCO on 8 July 2008. In the effort to promote heritage tourism, tourism authorities and businesses must be aware of the need to shift away from mass tourism towards a more responsible tourism. There must be a balance in sustainability and whether tourist development and consequences by tourist actors lead to responsible behavior. There is paucity of studies on tourist attitudes towards ‘green’ issues at tourist places. There is a need to explore tourists’ attitudes towards responsible tourism and this is crucial to Melaka as a WHS. The study proposes the development and validation of Responsible Heritage Tourism Scale (RHTS) to understand the concept of responsible tourism, awareness, acceptance and tourist behavior in choosing Melaka as heritage tourist destination. This listing of Melaka as WHS comes with commitment and responsibility, not just promoting heritage tourism but preserving cultural heritage as responsible tourism. The tradeoff between heritage and sustainability remains an issue. This study aims to analyze how authorities manage historic properties, cultures and the consequences of tourism actions, whether their concerns results in responsible behavior as well as challenges facing authorities & industries towards maintaining the listing status and preserving cultural heritage in the long run. Methodology will utilize triangulation approach. It will involve site visits and observation of heritage sites at Melaka. Elicitation procedure of items, item generation and scale judgment will follow to generate RHTS. 2 quantitative studies using surveys are used to validate RHTS. The study is of significance to Melaka government in formulating strategies towards tourism development and sustainable tourism in preserving cultural heritage sites and balancing tourism revenue with sustainability. RHTS can be applied to determine tourist attitudes in other WHS.